Cesarski gozdni vrt v Ljubljani - Perko, Franc (Gozdarski vestnik, 2021)
The article presents the initial ideas for the renewed forestation of Karst, from the first announcements of the government in Vienna that it would tackle it (1850), public discussion of how to regulate this (1850-151), and gathering of the Austrian Society on Karst and in Trieste from September 4 to 6, 1865, to the passing of the act on forestation of Karst in the Duchy of Carniola in 1885 (1881 for Trieste and surroundings; 1883 for Princely County Gorizia and Gradišča; 1886 for Istria). Carniola was getting prepared for foresting the Karst and founded the central forest tree nursery as early as in 1874, first below Rožnik in Ljubljana, from where it moved to Gradišče.
Keywords: Carniola; drevesnice; forestation; history; Karst; Kras; pogozditev; tree nurseries; zgodovina